Evaluating a multicomponent survivorship programme for men with prostate cancer in Australia: a single cohort study. Issue 2 (2nd February 2022) - Yates, Patsy; Carter, Rob; Cockerell, Robyn; Cowan, Donna; Dixon, Cyril; Lal, Anita; Newton, Robert U; Hart, Nicolas; Galvão, Daniel A; Baguley, Brenton; Denniston, Nicholas; Skinner, Tina; et al.
Abstract : Objective: To evaluate the implementation of a multicomponent survivorship programme for men with prostate cancer and their carers. Design: A single cohort study, guided by the RE-AIM framework. Setting: Multiple health services in Australia. Participants: Men with prostate cancer and their carers, and health professionals. Intervention: A 12-month telehealth programme that provided centralised and coordinated decision and information support, exercise and nutrition management, specialised clinical support and practical support to men and their carers. Data collection: Multiple sources of data including participant-reported health outcomes and experience of care, qualitative interviews, records of the programme were collected at different time points. Results: Reach: Of 394 eligible men at various stages of survivorship, 142 consented (36% consent rate) and 136 (96%) completed the programme. Adoption: All men participated in general care coordination and more than half participated in exercise and/or nutrition management interventions. Participation in the specialised support component (ie, psychosocial and sexual health support, continence management) was low despite the high level of need reported by men. Effectiveness: Overall, the men reported improvements in their experience of care. Implementation: Factors such as addressing service gaps, provision of specialised services, care coordination, adoption of needs-based and telehealth-based approaches were identified as enablers to the successful implementation of the programme. Issues such as insufficient integration with existing services, lack of resources and high caseload of the intervention team, men's reluctance to discuss needs and lack of confidence with technology were barriers in implementing the programme. Conclusion: Survivorship interventions are relevant to men regardless of the stage of their disease and treatments undertaken. It is possible to provide access to a comprehensive model of survivorship care to promote the health and quality of life for men with prostate cancer. Trial registration number: This study was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12617000174381).